Makanan Halal dalam Perspektif al-Qur’an, Sains dan Kesehatan: Halal Food in the Perspective of al-Quran, Science and Health - maftuhah maftuhah (Jurnal Bimas Islam, 2014)
Halal food and beverage are requirement for every moslem. Moslem believe that food and beverage that are consumed should be good and halal, because halal food and beverage gives significant influences in the spiritual and mental development. Along with the development of food technology that produces a lot of new products, It continues by a demand of halal law, both from the aspect of nutrition, ingredients, the way to make, media makers and other materials are not prohibited. Therefore, the enforcement of law JPH (Halal Food Guarantee) is the answer for securing consumers and producers. By JPH law, moslem society is expected to awake at the same time time raising community awareness about the importance of halal food and beverage as directed by the Qur’an and hadith.